EVALUATION OF ANTIBACTERIAL ACTIVITIES OF LATEX OF CARICACEAE (CARICA PAPAYA L.) - Islam, Aminul; MA, AL-MAMUN; S, PARVIN; MEH, SARKER; MK, ZAMAN; Parvin, Farhana; Zaman, Shahriar; M, SALAH UDDIN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Carica papaya Linn. belonging to the family of Caricaceae is a well-known fruit and medicinal plant that has been widely used for a long time to cure various types of infectious disease especially in South Asian countries. The current study was aimed to evaluate the antibacterial properties of crude latex of C. papaya. Methods: The screening of antibacterial activity of latex was evaluated against one Gram-positive bacterium Bacillus subtilis and three Gram-negative pathogenic bacterial strains as Escherichia coli, Agrobacterium sp and Rhizobium sp. Ciprofloxacin was used as a control for investigating the bacterial species. Antibacterial activity was expressed in terms of the radius of zone inhibition. Latex of this plant was tested in seven doses (1, 2, 5, 7, 10, 15 and 20 mg/disk) and it was found that the antibacterial activity was dose dependent and a significant difference was also observed in case of different bacterial stains. Results: The results demonstrated noticeable inhibition of the bacterial growth against the tested organisms. In case of Agrobacterium sp. 20 mg of latex showed the average of 20.66 mm zone of inhibition and for E. coli this value was 16 mm for the same concentration of latex. The rest of the two bacterial species showed comparative resistance to papaya latex. Conclusion: It is concluded that the latex of C. papaya probably contains some valuable antibacterial compounds that are crucial forinhibiting the growth of a wide variety of bacteria, especially Gram-negative bacteria and suggesting this for applying the treatment of a variety of bacterial infections. Keywords: Antibacterial activity, Bacteria, Escherichia coli, Carica papaya, Disk diffusion, Latex. Zoon inhibition.